Madagascar Economic Update, June 2018 : Fostering Financial Inclusion - World Bank Group (World Bank, Washington, DC, 2018)
Welcome to the June 2018 edition of the World Bank's Madagascar Economic Update, which reports on recent economic developments and presents our medium-term outlook. A special section of this Economic Update focuses on Financial Inclusion.